What components of emergency preparedness exercises improve healthcare practitioners' emergency response learning?. (August 2021) - Waring, Sara; Skryabina, Elena; Goodwin, Danielle; Lino, Denis; Amlôt, Richard
Abstract: Emergency planning exercises are commonly used to test the capability of healthcare systems to respond to major incidents. However, limited research has examined whether these exercises improve response learning for staff and, if so, what components are vital for achieving this learning. This study assesses the impact of an exercise methodology commonly used to promote emergency preparedness in UK healthcare staff, Emergo Train System (ETS), on healthcare practitioners' perceptions of learning regarding major incident response and identifies what components facilitate these perceptions of improved learning. A mixed method design was adopted, consisting of 83 pre- and post-exercise questionnaires and 10 semi-structured interviews collected from four ETS exercises. Paired Sample t-tests were conducted to identify changes in perceptions pre- and post-exercise, and stepwise multiple regression analysis was conducted to identify what exercise components facilitated perceptions of improved learning. Thematic analysis helped to understand further why healthcare practitioners felt these factors were important for improving learning. Findings showed that healthcare practitioners' confidence and perceptions of personal and organisational preparedness, multi-agency response and teamwork significantly improved post ETS. They believed that emergency response learning was facilitated by level of effort invested in preparatory activities prior to the exercise, exercise realism and frequency. Healthcare professionals believe that ETS exercises have the potential to improve emergency preparedness across individual, team, agency and multi-agency levels, provided that scenarios are realistic, relevant agencies and roles are involved, responders are able and motivated to invest in preparing for exercises, and exercises are run regularly.